d-Amino acids differentially trigger an inflammatory environment in vitro - Siew Hwei Yap; Cheng Siang Lee; Nur Diyana Zulkifli; Darshinie Suresh; Kenji Hamase; Kumitaa Theva Das; Reena Rajasuriar; Kok Hoong Leong (Amino Acids)
Abstract Studies in vivo have demonstrated that the accumulation of d-amino acids (d-AAs) is associated with age-related diseases and increased immune activation. However, the underlying mechanism(s) of these observations are not well defined. The metabolism of d-AAs by d-amino oxidase (DAO) produces hydrogen peroxide (H2O2), a reactive oxygen species involved in several physiological processes including immune response, cell differentiation, and proliferation. Excessive levels of H2O2 contribute to oxidative stress and eventual cell death, a characteristic of age-related pathology. Here, we explored the molecular mechanisms of d-serine (d-Ser) and d-alanine (d-Ala) in human liver cancer cells, HepG2, with a focus on the production of H2O2 the downstream secretion of pro-inflammatory cytokine and chemokine, and subsequent cell death. In HepG2 cells, we demonstrated that d-Ser decreased H2O2 production and induced concentration-dependent depolarization of mitochondrial membrane potential (MMP). This was associated with the upregulation of activated NF-кB, pro-inflammatory cytokine, TNF-α, and chemokine, IL-8 secretion, and subsequent apoptosis. Conversely, d-Ala-treated cells induced H2O2 production, and were also accompanied by the upregulation of activated NF-кB, TNF-α, and IL-8, but did not cause significant apoptosis. The present study confirms the role of both d-Ser and d-Ala in inducing inflammatory responses, but each via unique activation pathways. This response was associated with apoptotic cell death only with d-Ser. Further research is required to gain a better understanding of the mechanisms underlying d-AA-induced inflammation and its downstream consequences, especially in the context of aging given the wide detection of these entities in systemic circulation.